Investigation of malaria vectors Anopheles in non-endemic areas of Thailand: in proximity to workplaces housing foreign migrant workers - Nurhadi Eko Firmansyah; Thaksaporn Thongseesuksai; Thidarut Boonmars; Porntip Laummaunwai (Malaria Journal)
Abstract Background Foreign migrant workers from malaria-endemic regions play a critical factor in the transmission of malaria to non-endemic areas, mainly due to their mobility while seeking employment opportunities. This risk is particularly heightened in areas where malaria vectors are present. Methods This study aimed to investigate the malaria vectors in two sub-districts in Khon Kaen Province, known for their factory areas and the significant presence of Myanmar migrant worker communities. The collection was carried out from June 2020 to May 2021. The black light traps (BLT) operated continuously from 6:00 pm to 6:00 am (12 h) and Kelambu trap (KT) were set up from 6:00 pm to 9:00 pm, with both traps set up once a month. A total of 679 female Anopheles mosquitoes were collected near the workplaces and dormitories of these workers. Subsequently, the collected female mosquitoes underwent morphological identification using Standard Thailand keys and polymerase chain reaction analysis with rDNA ITS2 primers. Results Morphological identification revealed that 201 (29.6%) belonged to the Barbirostris complex. The remaining Anopheles mosquitoes are in the subgroup Cellia, comprised 437 (64.4%) Anopheles vagus, 39 (5.7%) Anopheles subpictus, and 2 (0.3%) Anopheles annularis. To distinguish the Barbirostris complex, multiplex PCR based on ITS-2 sequences was conducted. Out of the 201 specimens examined, 153 (76.1%) as Anopheles campestris, 36 (17.9%) as Anopheles wejchoochotei, and 12 (6%) as Anopheles dissidens. Additionally, the subgroup Anopheles Cellia was confirmed using specific primers based on ITS-2 sequences. Conclusions From the obtained results, An. campestris, An. wejchoochotei, An. vagus and An. annularis are reported as the malaria vectors in Thailand. The findings emphasized the important of addressing the presence of Anopheles malaria vectors, especially in the substantial migrant worker population originating from endemic areas. This situation raises concerns regarding the potential transmission of malaria infections to regions not traditionally affected by the disease. Epidemiological studies on malaria vectors should not solely concentrate on endemic regions but also extend to non-endemic areas because of the mobility of migrant workers throughout the country. This broader approach is crucial for implementing an effective malaria surveillance strategy. Graphical Abstract